Penerapan model pembelajaran kooperatif tipe jigsaw berbantu media kartu soal untuk meningkatkan prestasi belajar siswa mata pelajaran IPAS materi peranku di lingkungan sekolah dan masyarakat kelas IV SD Negeri 1 Penambongan - Abdullah, Husain; Pamujo (IKIP Siliwangi, 2025)
This study aims to improve students' learning achievement in the subject of science, especially in the material of my role in the school environment and society by implementing the jigsaw learning model and assisted by question card media. This type of research is classroom action research consisting of two cycles. The object of this study was 30 fourth grade students of SD Negeri 1 Penambongan. Consisting of 13 female and 17 male. The instruments used to collect data consisted of tests, observation sheets of teacher activities and student activities. The results of the study showed that the application of the jigsaw learning model can improve students' learning achievement in the material of my role in the school environment and society. These results are evidenced by the average student learning achievement in cycle I of 62.5 and classical completeness of 46.6% increasing in cycle II with an average value of 82.8 and classical completeness of 100%.